Sonic congealment and sculptural entropy in Bruce Nauman’s Anthro/Socio: expanding the theories of Rosalind Krauss - Chris Doyen (Cogent Arts & Humanities, 2025)
Bruce Nauman’s Anthro/Socio video installations provoke intense emotions in audiences. This article investigates sound as a key component to this phenomenon. Both Anthro/Socio (Rinde Facing Camera) (1991) and Anthro/Socio (Rinde Spinning) (1992) feature footage of performance artist Rinde Eckert loudly chanting ‘Feed Me, Eat Me, Anthropology’; ‘Help Me, Hurt Me, Sociology’; ‘Feed Me, Help Me, Eat Me, Hurt Me.’ The sound of these manic appeals, at such a high volume, assaults viewers’ sensibilities. The present study provides a theory involving sonic density, demonstrating how the formal mechanisms of the artwork—such as use of directional speakers to deliberately ‘isolate sound’—produce a dense acoustic architecture in the art gallery. An examination of how sound impacts the space around the image reveals the two-dimensional video image theoretically approaching the solidity of sculpture. In this sense, Anthro/Socio exemplifies Rosalind Krauss’s notion of the ‘post-medium condition’. This article also revises Krauss’s theory of ‘implosion’ concerning Nauman’s work ‘congealing’ space. With reference to Georges Bataille’s idea of the informe (formlessness), the present analysis expands Krauss’s application of the concepts of ‘pulse’ and ‘entropy’ to Nauman’s work, resulting in a realignment of sculptural aesthetics in relation to the spectator’s experience in the installation space.